Kepuasan Pasien Di Apotik Dahlia Berdasarkan Karakteristik Pasien Dengan Model SERVQUAL - Ningrum, Dwi Monika; Bayani, Faizul; Yuliana, Depi; Mukhlishah, Neneng Rachmalia Izzatul; Istri Widya Utamiswari, Cokorda (Jurnal Kesehatan Qamarul Huda, 2020)
Pharmacy services at the pharmacy are an integral part of the implementation of health efforts, which play an important role in improving the quality of health services for the community. The demands of patients and society for improving the quality of pharmaceutical services require an expansion from the old paradigm that is product oriented (drug oriented) to a new paradigm that is patient oriented (patient oriented) with a philosophy of pharmaceutical care. The purpose of this study was to see the level of patient satisfaction with prescription services at Dahlia Pharmacy Mataram. The sample in this study is part of the entire population who redeem prescriptions at the Dahlia Pharmacy with ages 19-65 years. The determination of the sample size with a confidence level of 99% using the Slovin formula. The results obtained by the level of patient satisfaction seen from each dimension include direct evidence (tangible), reliability, responsiveness, assurance, empathy shows that on average patients give a satisfied response to the service provided. This shows that the services provided by pharmacy officers are good enough. The study showed that the largest percentage of patients were satisfied with the services provided by the dahlia pharmacy by 67.96% and very satisfied with the percentage of 23.94%. It is known that the level of satisfaction obtained by customers is closely related to the quality standards of the goods or services they enjoy. The nature of satisfaction is subjective, but can be measured through the customer and community satisfaction index.